1999
DOI: 10.1254/jjp.80.229
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer Effect of Lafutidine on Indomethacin-Induced Gastric Antral Ulcers in Refed Rats

Abstract: Lafutidine is a new type antiulcer agent with antisecretory and gastroprotective activities. We investigated the effect of lafutidine on indomethacin-induced antral ulcer in refed rats. Subcutaneous indomethacin injection resulted in the formation of gastric antral ulcer. Lafutidine (1-10 mg/kg, p.o.) reduced the area of ulcer in a dose-dependent manner when administered immediately after the indomethacin injection. Capsaicin at 3 mg/kg, p.o. and 16,16-dimethyl prostaglandin E2 at 3 microg/kg, p.o. also reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…In addition to its antisecretory action, lafutidine is reported to exert a gastroprotective effect, which does not result from its antisecretory action, and also to promote mucin synthesis [10, 17]. The former effect was revealed to be mediated by capsaicin-sensitive sensory neurons [8, 9, 18]. However, there are no reports concerning direct interaction of lafutidine with the human H 2 R. Although the above-mentioned effects are beneficial, since lafutidine is an H 2 R antagonist, it is essential to determine the direct interaction of lafutidine with the human H 2 R. Herein, we describe, for the first time, the interaction of lafutidine with human H 2 Rs expressed in CHO cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its antisecretory action, lafutidine is reported to exert a gastroprotective effect, which does not result from its antisecretory action, and also to promote mucin synthesis [10, 17]. The former effect was revealed to be mediated by capsaicin-sensitive sensory neurons [8, 9, 18]. However, there are no reports concerning direct interaction of lafutidine with the human H 2 R. Although the above-mentioned effects are beneficial, since lafutidine is an H 2 R antagonist, it is essential to determine the direct interaction of lafutidine with the human H 2 R. Herein, we describe, for the first time, the interaction of lafutidine with human H 2 Rs expressed in CHO cells.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 13 demonstrates that after administration of lafutidine there is thickening of the surface mucus gel layer. In other studies using experimental animals, lafutidine has been shown to possess gastroprotective properties, such as strengthening the mucus gel layer, apart from its antisecretory activity (Ichikawa et al, 1994a;Onodera et al, 1999a;Sato et al, 2003). …”
Section: Effects Of Lafutidine On the Mucus Barriermentioning
confidence: 96%
“…The action of CGRP is in part mediated by endogenous NO. The gastroprotective action of lafutidine has been reduced or abolished by treatment with tetrodotoxin, CGRP 8-37 , or chemical defunctionalisation of afferent nerves (Mimaki et al, 2002;Onodera et al, 1999a), indicating that capsaicin-sensitive nerves contribute significantly to the mechanisms underlying the actions of lafutidine (Nishihara et al, 2002). Moreover, lafutidine has been shown to significantly increase CGRP release in both experimental animal models and humans (Harada & Okajima, 2007;Nishihara et al, 2002;Ikawa et al, 2006;Shimatani et al, 2006).…”
Section: Mechanisms Of Gastroprotective Actionsmentioning
confidence: 99%
“…famotidine, ranitidine, and cimetidine) [7] . In addition, lafutidine exerts gastroprotective effects independent of its antisecretory action [8,9] . Lafutidine has been shown to increase the gastric mucosal blood flow [9] and gastric mucus secretion [10,11] and to accelerate epithelial restitution in rats.…”
Section: Lafutidine (±)-2-(furfuryl Sulfinyl)-n-[4-[4-(piperidinometmentioning
confidence: 99%